2010
DOI: 10.1017/s0007114510000218
|View full text |Cite
|
Sign up to set email alerts
|

Mulberry fruit protects dopaminergic neurons in toxin-induced Parkinson's disease models

Abstract: Parkinson's disease (PD), one of the most common neurodegenerative disorders, is characterised by the loss of dopaminergic neurons in the substantia nigra pars compacta (SNpc) to the striatum (ST), and involves oxidative stress. Mulberry fruit from Morus alba L. (Moraceae) is commonly eaten, and has long been used in traditional oriental medicine. It contains well-known antioxidant agents such as anthocyanins. The present study examined the protective effects of 70 % ethanol extract of mulberry fruit (ME) agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
102
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(107 citation statements)
references
References 41 publications
4
102
0
1
Order By: Relevance
“…This effect may stem primarily from its antioxidant activities such as its repression of ROS generation and up-regulation of SOD, CAT, and GSH expression (which follow the induction of Nrf2 expression). The CSE used in this study contained 47.06 mg/g fatty acids, which were found in gas chromatography analyses to be mostly of medium chain length (C [16][17][18] ). The major fatty acids were linoleic acid and linolenic acid (accounting for 30.34 and 38.05% of fatty acids, respectively; table 1 ), which have been reported in previous studies to have antioxidative and therapeutic effects in various skin diseases [23][24][25][26] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect may stem primarily from its antioxidant activities such as its repression of ROS generation and up-regulation of SOD, CAT, and GSH expression (which follow the induction of Nrf2 expression). The CSE used in this study contained 47.06 mg/g fatty acids, which were found in gas chromatography analyses to be mostly of medium chain length (C [16][17][18] ). The major fatty acids were linoleic acid and linolenic acid (accounting for 30.34 and 38.05% of fatty acids, respectively; table 1 ), which have been reported in previous studies to have antioxidative and therapeutic effects in various skin diseases [23][24][25][26] .…”
Section: Resultsmentioning
confidence: 99%
“…DCFH-DA enters cells passively and is converted into nonfluorescent DCFH, which reacts with ROS to form the fluorescent product DCF [18] . HaCaT cells were seeded on black 96-well plates or onto coverslips in 24-well plates and treated with CSE at doses of 100 and 500 g/ml for 1 h. Then, they were stimulated with 1 m M H 2 O 2 for an additional 30 min.…”
Section: Measuring Cell Viabilitymentioning
confidence: 99%
“…Parkinson's disease (PD) is the most prevalent neurodegenerative disorder and occurs more frequently among the elderly; PD has become the second largest killer of the elderly [1,2]. PD is characterized by a large loss of dopamine (DA) neurons in the substantia nigra pars compacta (SNc) of the midbrain [3].…”
Section: Introductionmentioning
confidence: 99%
“…It is also used for treating weakness, fatigue, anemia and premature graying of hair. Recently, several lines of evidence have demonstrated that mulberry fruits can protect against brain damage in various conditions including Parkinson's disease (Kim et al, 2010), cerebral ischemia (Kang et al, 2006) and alcohol neurotoxicity. In addition, the memory impairment and the elevated acetyl cholinesterase induced by alcohol toxicity are also reversed.…”
Section: Introductionmentioning
confidence: 99%